2017
DOI: 10.1021/acs.jpcb.7b00433
|View full text |Cite
|
Sign up to set email alerts
|

Complex, Dynamic Behavior of Extremely Asymmetric Di-n-Alkylphosphate-Anion Aggregates, the Long-Chain Effect and the Role of a Limiting Size: Cryo-TEM, SANS, and X-Ray Diffraction Studies

Abstract: For extremely asymmetric n-hexyl(n-decyl)phosphate (HDeP), n-hexyl(n-dodecyl)phosphate (HDoP), and n-hexyl(n-cetyl)phosphate (HCeP), the effect of the long-chains on the dynamic behavior of their aggregate structures in water was examined by cryo-TEM imaging, SANS, and X-ray diffraction techniques. The cryo-TEM images demonstrated the complex and dynamic behavior of the aggregates, and its dependence on the length of the long-chain. Application of the one-dimensional aggregate theory to the SANS results led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…Considering the X-ray crystallographic data for CPZHCl in the solid-state [43], this value is indicative of a surfactant bilayer. Following the Bragg equation, it has been suggested that the diffuse, wide-angle feature corresponds to the intraaggregate spacings (d = 4.4 Å) between the alkyl chains attached to the N-X position on individual CPZHCl molecules, as similar values (4.5 Å) have been proposed for the spacings between alkyl chains within XYZ lyotropic liquid crystals [44]. Taken together with reported NMR data [45], this implies that the CPZ.HCl molecules aggregate together in a "cup-stack" arrangement and on top of each other, with the hydrophobic core comprising the aromatic rings, and the alkyl chains penetrating the aqueous pseudo phase enabling the formation of a micellar palisade layer.…”
Section: Electrochemical Characterisation Of Cpzhcl-llcsmentioning
confidence: 79%
“…Considering the X-ray crystallographic data for CPZHCl in the solid-state [43], this value is indicative of a surfactant bilayer. Following the Bragg equation, it has been suggested that the diffuse, wide-angle feature corresponds to the intraaggregate spacings (d = 4.4 Å) between the alkyl chains attached to the N-X position on individual CPZHCl molecules, as similar values (4.5 Å) have been proposed for the spacings between alkyl chains within XYZ lyotropic liquid crystals [44]. Taken together with reported NMR data [45], this implies that the CPZ.HCl molecules aggregate together in a "cup-stack" arrangement and on top of each other, with the hydrophobic core comprising the aromatic rings, and the alkyl chains penetrating the aqueous pseudo phase enabling the formation of a micellar palisade layer.…”
Section: Electrochemical Characterisation Of Cpzhcl-llcsmentioning
confidence: 79%
“…About 3.0–3.3 mg of samples were sealed in aluminum sample pans and the heat flow was measured against alumina as a reference. Temperature scans from 25 to 80 °C was performed for each sample at rates of 3 K min –1 . …”
Section: Methodsmentioning
confidence: 99%